Pelatihan Digital Marketing di Madrasah Tsanawiyah Azzidin Medan Denai untuk Meningkatkan Jumlah Siswa Baru - Firmansyah, Edy; Tulim, Anto; Siregar, Ilhamsyah; Syaukani, Arham; Napitupulu, Dea Okviar Egano (EMPOWERMENT: Journal of Community Practice, 2025)
Madrasah Tsanawiyah Azzidin Medan, which was opened in 2010, is a junior high school-level madrasah in Medan City. At that time, this madrasah had 123 students. Madrasah Tsanawiyah Azzidin Medan had 85% of students in 2023, but in 2024 the number dropped to 73 students. This madrasah strives to produce marketing personnel who are able to improve accurate communication in digital media and tend to be objective. Continuous training is needed, where this training aims to improve the ability to promote through effective communication in order to increase the number of new students at Madrasah Tsanawiyah Azzidin Medan. The materials used for this training are wifi networks, materials for creating marketing websites via computers, laptops, complete hardware and software, and books on communication techniques in advertising, while the method of implementing community service is carried out using lecture, practice and simulation methods, where the results of implementing community service through digital marketing training from the Azzidin Medan Middle School can increase the understanding and knowledge of training participants about digital marketing by 85% of the total 37 participants who attended.